2020
DOI: 10.3390/agronomy10122004
|View full text |Cite
|
Sign up to set email alerts
|

Differential Influence of No-Tillage and Precipitation Pulses on Soil Heterotrophic and Autotrophic Respiration of Summer Maize in the North China Plain

Abstract: It is important to strengthen the studies on the response of soil respiration components to tillage practices and natural precipitation in cropland. Therefore, soil heterotrophic respiration (RH) and autotrophic (RA) respiration were monitored by a root exclusion method in the North China Plain (NCP). The tillage practices included no-tillage (NT) and conventional tillage (CT), and the study periods were the summer maize growth stages in 2018 and 2019. RH, RA, soil water content and temperature were measured c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In future research, microbial biomass, microbial diversity, and partitioning between autotrophic and heterotrophic respiration would further improve our understanding on the long-term effect of tillage. For example, Du et al [53] found that soil autotrophic respiration is lower in P compared to NT, while heterotrophic respiration is higher in P, but this relation is affected by rainfall (soil moisture changes). All these environmental effects and the different reaction of soil microbes to temperature and moisture changes affect greenhouse gas emissions in the end, but soil microbial respiration provides information on the general activity of microbes.…”
Section: Biological Parametersmentioning
confidence: 99%
“…In future research, microbial biomass, microbial diversity, and partitioning between autotrophic and heterotrophic respiration would further improve our understanding on the long-term effect of tillage. For example, Du et al [53] found that soil autotrophic respiration is lower in P compared to NT, while heterotrophic respiration is higher in P, but this relation is affected by rainfall (soil moisture changes). All these environmental effects and the different reaction of soil microbes to temperature and moisture changes affect greenhouse gas emissions in the end, but soil microbial respiration provides information on the general activity of microbes.…”
Section: Biological Parametersmentioning
confidence: 99%
“…The soil type is a calcaric Fluvisol, and the texture of the surface soil is silt loam (sand, 12%; silt, 66%; clay, 22%). In the top 20 cm of the soil layer, the mean pH (soil: water, 1:5) was 8.3, total organic content was 12.6 g kg −1 , total N was 0.89 g kg −1 , total P was 2.11 g kg −1 , and total K was 21.4 g kg −1 [30,31].…”
Section: Site Descriptionmentioning
confidence: 99%
“…The detailed information of the RZWQM2 could refer the study of Ahuja et al [33]. The simulation of SWC used the measured air temperature, air humidity, wind speed, rainfall and soil physical parameters in the module of SWC physical transfer process, and soil nutrients were input into the related nutrients module [30,31,33,34]. The Brooks Corey equation was used to describe the soil moisture characteristic curve, and the Richards equation was used to measured soil water redistribution between soil layers [33,34].…”
Section: Simulation and Validation Of Swc And Crop Biomassmentioning
confidence: 99%
“…From mid-July 2020, field comparison testing was conducted at the Shandong Yucheng Agro-ecosystem National Observation and Research Station, Ministry of Science and Technology (36 • 50 N, 116 • 34 E). Detailed environment and cropland management information on this station can be found in previous studies [25][26][27][28]. An ET60 instrument (Insentek Oriental Sense of WisdomTechnology Co. Ltd., Hangzhou, China) was installed as the control instrument after soil punching and grouting [29].…”
Section: Field Measurementmentioning
confidence: 99%